Study of harmful gas migration law and influencing factors after tunnel blasting in high-altitude tunnels under push ventilation conditions - Shigui Fu; Zegong Liu; Jinwei Qiu; Shuai Yang; Guodong Qiao; Gangjian An (Scientific Reports)
Abstract Multiple toxic gases, such as carbon monoxide (CO), are generated after blasting of plateau tunnel. To investigate the migration patterns of CO during the ventilation process following blasting in high-altitude tunnels, this paper employs a three-dimensional model of tunnel blasting excavation under push ventilation. The study utilizes computational fluid dynamics to explore the temporal and spatial evolution characteristics of CO under various operational conditions. The influence of relevant factors was quantified using the grey relational analysis method. Numerical simulations were then used to derive distribution functions for CO concentration in relation to altitude, ventilation time, and other factors. The results indicate that under the influence of push ventilation, multiple vortex regions form due to the interaction between ventilation jets and several recirculation areas, where the airflow velocity is slower and CO concentrations are higher compared to other nearby regions. The grey relational analysis method yielded correlation factors of 0.634039, 0.6572, and 0.6560 for altitude (H), distance from duct outlet to working face (L 0), and ventilation volume (Q), respectively. Notably, altitude plays a significant role in CO migration; as altitude increases from 0 to 6000 m, the peak CO equivalent mass concentration at the tunnel exit increases by 77.10%. A correction coefficient K H  = exp(0.0952H) was derived for the relationship between altitude and CO concentration peaks. Finally, the CO distribution function based on tunnel ventilation parameters is established. The derived formula was compared with actual field data, confirming that this distribution function can guide environmental safety assessments following tunnel blasting.